Negotiating the Boundaries of Gender in Religious Life: Robert of Arbrissel and Hersende, Abelard and Heloise - Mews, Constant J. (Viator, 2006)
Abstract This article explores a range of connections between the foundation of Fontevraud by Robert of Arbrissel and Hersende, its first prioress, and of the Paraclete by Abelard and Heloise, arguing that both communities were characterized by uncertainty and controversy about gender roles. It explores Abelard’s support for Robert, against the criticisms of Roscelin, yet distrust of the practice of an abbess having authority over both men and women, as happened when Petronilla became abbess in 1115. In particular it supports Robl’s hypothesis that Hersende of Fontevraud was the same person as Hersende, mother of Heloise. Fulbert’s willingness to have Heloise educated by Abelard reflects the same literary values as Baudri of Bourgueil, a great admirer of Robert of Arbrissel. Heloise’s assertion of her role as abbess of the Paraclete reflects her awareness, not shared by Abelard, that it was necessary for her to emulate Petronilla as abbess with authority of both men and women.